Optimal configuration algorithm for static segment of FlexRay - Yong XIE; Ren-fa LI; Hua-bin RUAN; Xin PENG (Tongxin xuebao)
FlexRay,which could provide high data bandwidth,time determinism and reliability,was recognized as the standard of the next generation automotive buses,but the complexity of the configuration hindered its wide application in automotive electronics systems.Slot ID assignment of static segment was the key part of its configuration.Started from the system-level point of view,a new system-level scheduling unit model was defined.Based on confining the iable slot IDs and analyzing delay for each scheduling unit,a branch and bound-based searching was carried on to search the optimal slot ID assignment plan that realized the minimization of system’s end-to-end delay.Both theoretical proving and experimental results show that the slot ID assignment method is optimal in optimizing system’s end-to-end delay.